lncRNA TRMP-S directs dual mechanisms to regulate p27-mediated cellular senescence - Tian Shuai; Muhammad Riaz Khan; Xu Dong Zhang; Jingmin Li; Rick Francis Thorne; Mian Wu; Fengmin Shao (Elsevier, 2021)
Long noncoding RNAs (lncRNAs) undergo extensive alternative splicing, but little is known about isoform functions. A prior investigation of lncRNA RP11-369C8.1 reported that its splice variant TRMP suppressed p27 translation through PTBP1. Here we characterize a second major splice variant, TRMP-S (short variant), whose enforced loss promotes cancer cell-cycle arrest and p27-dependent entry into cellular senescence. Remarkably, despite sharing a single common exon with TRMP, TRMP-S restrains p27 expression through distinct mechanisms. First, TRMP-S stabilizes UHRF1 protein levels, an epigenetic inhibitor of p27, by promoting interactions between UHRF1 and its deubiquitinating enzyme USP7. Alternatively, binding interactions between TRMP-S and FUBP3 prevent p53 mRNA interactions with RPL26 ribosomal protein, the latter essential for promoting p53 translation with ensuing suppression of p53 translation limiting p27 expression. Significantly, as TRMP-S is itself transactivated by p53, this identifies negative feedback regulation between p53 and TRMP-S. Different splicing variants of the RP11-369C8.1 gene thereby exert distinct roles that converge on the homeostatic control of p27 expression, providing an important precedent for understanding the actions of alternatively spliced lncRNAs.